PENGARUH INTERAKSI PARASOSIAL PADA KONTEN SARA WIJAYANTO “DIARY MISTERI SARA” TERHADAP KESEHATAN MENTAL SARADDICTS SURABAYA - Ninis Abiyu Ghinanda, Labibah; Zusyana D, Ratnaningrum; Lailiyah, Fatihatul (Universitas Islam Majapahit, Indonesia, 2021)
In social life, if humans never communicate with other people, they will be isolated from the environmentPublic. The influence of this isolation will certainly bring up mental stress which in the end brings people out of balance(mental disorders). Sara Wijayanto's mystical genre content with the title